Cost-effectiveness Analysis of Hypoallergenic Milk Formulas for the Management of Cow’s Milk Protein Allergy in the United Kingdom - Rui Martins; Mark P. Connolly; Eleanor Minshall (Journal of Health Economics and Outcomes Research)
**Background:** Cow’s milk protein allergy (CMPA) is the most common food allergy in early childhood. In most children CMPA resolves by age 5 or 6; however, if not treated correctly can provoke nutritional deficiency resulting in poor growth. Management consists of excluding cow’s milk from the diet, with hypoallergenic formulas (or non-dairy alternatives) being introduced to meet nutritional requirements.